The Changing Way Governments Talk about Poverty and Inequality : Evidence from Two Centuries of Latin American Presidential Speeches - Calvo-Gonzalez, Oscar; Eizmendi, Axel; Reyes, German (World Bank, Washington, DC, 2018)
This study uses text mining techniques on almost 900 presidential "state-of-the-union"--type speeches from 10 Latin American countries from 1819 to 2016. The paper documents a sharp increase in recent decades in references to poverty and inequality. The study's long-term view shows that the way in which poverty and inequality are discussed has been changing. Using a Latent Dirichlet Allocation algorithm, the paper shows that in recent years poverty has been increasingly discussed as a broader multidimensional challenge that requires a variety of social programs. Inequality has been increasingly framed as an issue of equal opportunities, whereas previously there was a greater focus on social justice. The paper assesses whether the prevalence of poverty and inequality in presidential speeches correlates with measures such as social public spending, as well as the poverty and inequality levels of the country. It finds that during the 2000s, the countries that discussed poverty and inequality at greater length were also the ones that increased social spending and reduced poverty and inequality the most.